2023
DOI: 10.3389/fenvs.2022.1058792
|View full text |Cite
|
Sign up to set email alerts
|

Simulation, prediction and driving factor analysis of ecological risk in Savan District, Laos

Abstract: Introduction: In recent years, Laos, with its unique geographical advantages, has vigorously developed overseas trade and cultural tourism industry, which has promoted local economic development and introduced numerous ecological and environmental problems.Method: Therefore, this research took Savan District as the research area, built the landscape ecological risk assessment model to reveal the spatiotemporal evolution characteristics of Savan District’s ecological risk from 2000 to 2020. Then, the Geodetecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…These were the landscape fragmentation, isolation, dominance, disturbance, vulnerability, and loss indices (Table 2). The moving window method using a 15-km window was applied in Fragstats 4.2 to calculate the landscape pattern index of Laos (Bai and Weng, 2023;Xu et al, 2023). The window was moved from the left, upper section of the study area, and progressed at a single-grid step.…”
Section: Methods Used To Analyze the Landscape Pattern Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…These were the landscape fragmentation, isolation, dominance, disturbance, vulnerability, and loss indices (Table 2). The moving window method using a 15-km window was applied in Fragstats 4.2 to calculate the landscape pattern index of Laos (Bai and Weng, 2023;Xu et al, 2023). The window was moved from the left, upper section of the study area, and progressed at a single-grid step.…”
Section: Methods Used To Analyze the Landscape Pattern Indexmentioning
confidence: 99%
“…The geodetector used in the present study incorporated risk factor, ecological, and interaction detectors (Zhu et al, 2020). The present study selected the factor detector for use in the geodetector through reference to relevant previous research results (Huang et al, 2020;Liang et al, 2022;Xu et al, 2023). The present study identified 14 socioeconomic and regional accessibility factors affecting the landscape ecological hazard in Laos, including the digital elevation model (DEM), slope, fractional vegetation cover, annual average temperature, annual precipitation, organic matter content, population density, kilometer grid GDP, night light, distance from the road, distance to water, distance from the town center, and distance to parks and reserves.…”
Section: Analysis Of the Geodetector Attributionmentioning
confidence: 99%
“…Based on the relevant studies [67][68][69] and the experimental comparisons, we reclassified the forest fragmentation severity of each analytical unit into five grades: low fragmentation, above-low fragmentation, medium fragmentation, sub-high fragmentation, and high fragmentation, by following the criteria of natural breakpoint reclassification.…”
Section: Detection Of Factors Associated With Forest Fragmentationmentioning
confidence: 99%
“…Climate change and human activities pose increased risks to ecosystems and sustainable development [3,4]. The ecological environment is a prerequisite for social and economic development and a necessary safeguard for human survival [5]. The LERI reveals unfavourable consequences arising from natural or human activity [6].…”
Section: Introductionmentioning
confidence: 99%